Synchrotron radiation x-ray photoelectron spectroscopic study of CdTe-in structures formed by laser-induced doping technique - Kateryna Zelenska; Volodymyr Gnatyuk; Wanichaya Mekprasart; Wisanu Pecharapa; Hideki Nakajima (My University, 2018)
Laser-based doping technique was used in the fabrication of M-p-n structured In/CdTe/Au diodes which are sensitive to X- and γ-rays. CdTe is transparent for infrared radiation that allows irradiating the CdTe-In structures in two different ways: from metal side or through the semiconductor. The obtained In/CdTe/Au diodes were tested by electrical measurements and demonstrated low leakage current and high forward current. The distribution of In and Cd atoms with the depth in the irradiated In-CdTe structures was studied by X-ray photoelectron spectroscopy (XPS) using synchrotron radiation as the excitation light. The excitation energy was 650 eV. The In film, deposited on the CdTe crystal, was sputtered by 3 keV Ar ions during 2 hours between spectra measurements. Total time of sputtering was 10 hours. The XPS spectra for non-irradiated sample, irradiated from the In film side and through the CdTe crystal by 10 infrared laser pulses with power density of 2.5 MW/cm2 were studied. Photoelectron peaks of Cd 3d and In 3d were analyzed. The evidences of laser-induced evaporation of the In film, stress-wave-induced mass transfer, freezing of non-equilibrium defects and subsequent dissolution of CdTe in the laser-molten thin layer of In film are discussed.
Keywords: Cadmium telluride photovoltaics; Advanced Semiconductor Detectors and Materials